Research on Runoff Simulation of Arid Oasis Irrigation Area Based on SWAT Model - JIANG Mengyao; WANG Shuixian; ZHAO Zhigang (Renmin Zhujiang)
In order to study the runoff changes in the arid oasis irrigation area,this paper constructs a distributed hydrological model of Yanqi Basin based on SWAT model with the Chinese meteorological assimilation driving datasets (CMADS) from 1955 to 2017,traditional hydrometeorological station data,land use data,soil data,digital elevation data,analyzes the sensitivity of parameters by SUFI-2 (Sequential Uncertainty Fitting) algorithm,calibrates several important parameters influencing runoff simulation results through SWAT-CUP (SWAT Calibration Uncertainty Procedures) software,and verifies the model by the measured runoff from 1991 to 2017.The results show that:the simulated runoff of Yanqi Basin in Xinjiang for a long time scales coincides with the measured runoff.During the calibration period and verification period,the Nash coefficient (NES) is above 0.82,the Pearson correlation coefficient (R2) is 0.86 and 0.90 respectively,and the relative error (Re) is less than 10.Therefore,SWAT model is well applicable to the runoff simulation of Yanqi Basin.Based on this,runoff changes from 2016 to 2100 in Yanqi Basin under the scenarios of RCP4.5 and RCP8.5 are simulated.It can be found that precipitation changes in Kaidu River basin have a significant impact on runoff in Yanqi Basin,that is,when precipitation increases by 20% and temperature increases by 2°C,the runoff increases by 26.53% compared with the current year.